Within the enclave Profiling South African social and religious developments since 1994 - Johan Cilliers; Ian A. Nell (Verbum et Ecclesia, 2011)
The paper investigated religious and social transformations within a specific religious tradition in South Africa. After clarifying the charged concept of transformation, the authors showed that transformation is about more than changed systems and structures, for, on a deeper level, it is also about the change in relationships and attitudes between the different cultural groups in South Africa. The argument was supported by making use of data from the SA reconciliation barometer 2010 and the 2009 Transformation audit. In the next part of the paper, the authors took a closer look at the Dutch Reformed Church (DRC) as a case in point. The basic question they asked was how do these social transformations affect the religious transformations within the DRC and vice versa? By making use of Mary Douglass concept of the enclave it was proposed that a new enclave developed in the DRC after 1994, the characteristics of which were investigated in the remainder of the paper.